Wireless receiver design for digital communications - McClaning, Kevin 1959- (Raleigh, NC SciTech Publishing, 2012)
The book reviews developments in the following fields: wireless receiver design; digital communication; radio frequency basics; signal; noise; modulation; propagation; antenna; filter; mixer; oscillator; cascade design; and demodulation.
Rev. ed. of Radio receiver design / Kevin McClaning, Tom Vito. 2000.
Electronic reproduction.
Keywords: Radio -- Receivers and reception -- Design and construction; Digital communications; Antennas (Electronics).; Demodulation (Electronics).; Electric filters; Mixing circuits; Oscillators, Electric; Electronic books